A Comparative Study for the Proton Electronic Stopping Power of Some Polymers by Using Mathematica, SRIM2013, PSTAR, LibdEdx, and Experimental Databases - Jassim, Mustafa Kamil (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The available experimental data of proton electronic stopping power for Polyethylene, Mylar, Kapton and Polystyrene are compared with Mathematica, SRIM2013, PSTAR and libdEdx programs or databases.  The comparison involves sketching out both experimental and databases data for each polymer to discuss the agreement. Further, we use statistical means via standard deviation resulting from the mean normalized difference to describe the precise agreement among the databases and the experimental data. We found that there is not a specific one database can describe the experimental data for certain material at given proton energy.